2013
DOI: 10.4103/0253-7613.108294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adverse reactions of antiretroviral drug regimens in a tertiary care hospital

Abstract: Objectives:Antiretroviral toxicity is an increasingly important issue in the management of HIV-infected patients. The objective of our study was to evaluate the toxicity profile of currently used antiretroviral regimens and to compare these toxicities among males and females.Materials and Methods:A retrospective analysis with a one year follow-up was done at a tertiary care hospital by reviewing the record. Patients who were >18 years of age attending the hospital and were initiated an antiretroviral drug regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Peripheral neuropathy, anaemia, hepatitis and gastritis were the most prevalent DIDs with use of highly active anti-retroviral therapy (HAART) treatment in the study of Anwikar et al 28 . Rather et al 29 reported anaemia, hepatic toxicity, itching, skin rash, elevated triglycerides and peripheral neuropathy to be the most common DIDs in their study due to ART. Common cardiovascular adverse drug events reported were drug-induced arrhythmias, blood pressure abnormalities and heart failure 22 .…”
Section: Discussionmentioning
confidence: 91%
“…Peripheral neuropathy, anaemia, hepatitis and gastritis were the most prevalent DIDs with use of highly active anti-retroviral therapy (HAART) treatment in the study of Anwikar et al 28 . Rather et al 29 reported anaemia, hepatic toxicity, itching, skin rash, elevated triglycerides and peripheral neuropathy to be the most common DIDs in their study due to ART. Common cardiovascular adverse drug events reported were drug-induced arrhythmias, blood pressure abnormalities and heart failure 22 .…”
Section: Discussionmentioning
confidence: 91%
“…This also substantiates our findings that anti-tubercular and antiretroviral drugs are known to cause skin reactions and liver damage. [181920] Probably, this supports cohort monitoring and integration of Revised National Tuberculosis Control Programme and ART programme with nationwide PvPI. In addition, it has been reported by Agaard et al .…”
Section: Discussionmentioning
confidence: 67%
“…Treated with antiretroviral therapy, HIV-infected individuals are living longer but prone to the potentially neurotoxic effects of antiretroviral therapy ( Gabbai et al ., 2013 ). Antiretroviral toxicity is an increasingly important issue in the management of HIV-infected patients ( Rather et al ., 2013 ). The neuropathic pain caused by DSP is very difficult to manage with few options available.…”
Section: Discussionmentioning
confidence: 99%